Sistem Pendukung Keputusan Pemilihan Personel Homeband Universitas Brawijaya Menggunakan Metode Profile Matching - Aditya Sudarmadi; Edy Santoso; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Brawijaya Homeband University is a part of Students Unit Activities which has 2 years of regulation. In maintaining its existence, a selection is held in every 2 years. One of the problems was faced in previous selection was unclear scoring mechanism. This problem made the duration in selecting the member of the homeband longer. Moreover, the selection result was subjective. This manual mechanism is not an efficient meachanism, moreover when the participants are more than before. Research of Decission Suport System for Members Homeband Brawijaya University selection was using profile match technique. The positions which were wanted were male Vocalist, female vocalist, guitarist, bassist, keyboardist and drummer. Every position has 6 scoring factors which consist of 4 core factors and 2 secondary factors. The result of this research shows the accuracy system was 83.8%, 5 of 6 members selected by the system are the members who also selected by the judges. Therefore, it can be concluded the result of this research can be used for assisting the Homeband of Brawijaya University member's selection.